2011
DOI: 10.1007/s11325-010-0456-y
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant status in patients with obstructive sleep apnea without comorbidities: the role of the severity of the disease

Abstract: The present study supports a reduction in antioxidant capacity during sleep in otherwise healthy patients with OSAS. This reduction was evident in less severe syndrome. However, a single night of CPAP application seems to ameliorate this antioxidant disturbance only in less severe syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…On the one hand, decreased total anti-oxidant status was described in adults with OSA compared to healthy controls and an inverse linear relationship between anti-oxidant capacity and AHI in adults was reported [48, 62]. However, others have observed lower total anti-oxidant levels in adults with mild to moderate but not severe OSA[63]. In the present study, lower serum alpha tocopherol and beta carotene normalized to total serum lipids were observed in NAFLD patients with OSA/hypoxia compared to lean controls.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, decreased total anti-oxidant status was described in adults with OSA compared to healthy controls and an inverse linear relationship between anti-oxidant capacity and AHI in adults was reported [48, 62]. However, others have observed lower total anti-oxidant levels in adults with mild to moderate but not severe OSA[63]. In the present study, lower serum alpha tocopherol and beta carotene normalized to total serum lipids were observed in NAFLD patients with OSA/hypoxia compared to lean controls.…”
Section: Discussionmentioning
confidence: 99%
“…Yamauchi et al [39] found increased urinary 8-hydroxy-20-deoxyguanosine (8-OhdG) excretion in the severe OSA patients, Carpagnano et al [10] observed elevated 8-isoprostane levels in the exhaled breath condensate in OSA patients and Dyugovskaya et al [40] detected an increase in the production of ROS in OSA. Several other studies reported abnormal lipid peroxidation in OSAS [7,8] or reduced total antioxidant status [9]. Conversely, Wali et al [41] found no differences in susceptibility of LDL to oxidative stress and Svatikova et al [42] reported that patients with moderate – severe OSA did not have evidence for greater oxidative stress and lipid peroxidation than healthy normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Katsoulis et al reported some unexpected results where they found that total antioxidant status before and after sleep was significantly lower in OSA patients with AHI < 30 (1.73 versus 1.65 mmol/L, P = 0.01) but not in severe OSA patients with AHI > 30 (1.64 versus 1.58 mmol/L, P = 0.07). A possible explanation could be due to differences between the acute effects of hypoxia resulting from apneic sleep and chronic oxidative stress that may be sustained in severe OSA patients even during the daytime [53]. …”
Section: Oxidative Stress In Osamentioning
confidence: 99%